Deciphering the Antibacterial Mechanisms of 5-Fluorouracil in Escherichia coli through Biochemical and Transcriptomic Analyses - Muchen Zhang; Huangwei Song; Siyuan Yang; Yan Zhang; Yunrui Tian; Yang Wang; Dejun Liu (MDPI AG, 2024)
The emergence of carbapenem-resistant Gram-negative pathogens presents a clinical challenge in infection treatment, prompting the repurposing of existing drugs as an essential strategy to address this crisis. Although the anticancer drug 5-fluorouracil (5-FU) has been recognized for its antibacterial properties, its mechanisms are not fully understood. Here, we found that the minimal inhibitory concentration (MIC) of 5-FU against Escherichia coli was 32-64 µg/mL, including strains carrying blaNDM-5, which confers resistance to carbapenems. We further elucidated the antibacterial mechanism of 5-FU against E. coli by using genetic and biochemical analyses. We revealed that the mutation of uracil phosphoribosyltransferase-encoding gene upp increased the MIC of 5-FU against E. coli by 32-fold, indicating the role of the upp gene in 5-FU resistance. Additionally, transcriptomic analysis of E. coli treated with 5-FU at 8 µg/mL and 32 µg/mL identified 602 and 1082 differentially expressed genes involved in carbon and nucleic acid metabolism, DNA replication, and repair pathways. The biochemical assays showed that 5-FU induced bacterial DNA damage, significantly increased intracellular ATP levels and the NAD+/NADH ratio, and promoted reactive oxygen species (ROS) production. These findings suggested that 5-FU may exert antibacterial effects on E. coli through multiple pathways, laying the groundwork for its further development as a therapeutic candidate against carbapenem-resistant bacterial infections.